Cell immunity to SARS-CoV-2 after natural infection and/or different vaccination regimens - Culebras, Esther; Martínez, Mercedes; Novella, Consuelo; León, Jose Manuel; Marcos, Esther; Delgado-Iribarren, Alberto; Ríos, Esther (Frontiers in Cellular and Infection Microbiology, 2024)
Background: The aim of the study was to evaluate the humoral and cellular immunity after SARS-CoV-2 infection and/or vaccination according to the type of vaccine, number of doses and combination of vaccines. Methods: Volunteer subjects were sampled between September 2021 and July 2022 in Hospital Clínico San Carlos, Madrid (Spain). Participants had different immunological status against SARS-CoV-2: vaccinated and unvaccinated, with or without previous COVID-19 infection, including healthy and immunocompromised individuals. Determination of IgG against the spike protein S1 subunit receptor-binding domain (RBD) was performed by chemiluminescence microparticle immunoassay (CMIA) using the Architect i10000sr platform (Abbott). The SARS-CoV-2-specific T-cell responses were assessed by quantification of interferon gamma release using QuantiFERON SARS-CoV-2 assay (Qiagen). Results: A total of 181 samples were collected, 170 were from vaccinated individuals and 11 from unvaccinated. Among the participants, 41 were aware of having previously been infected by SARS-CoV-2. Vaccinated people received one or two doses of the following vaccines against SARS-CoV-2: ChAdOx1-S (University of Oxford—AstraZeneca) (AZ) and/orBNT162b2 (Pfizer—BioNTech)(PZ). Subjects immunized with a third-booster dose received PZ or mRNA-1273 (Moderna—NIAID)(MD) vaccines. All vaccinees developed a positive humoral response (>7.1 BAU/ml), but the cellular response varied depending on the vaccination regimen. Only AZ/PZ combination and 3 doses of vaccination elicited a positive cellular response (median concentration of IFN- γ > 0.3 IU/ml). Regarding a two-dose vaccination regimen, AZ/PZ combination induced the highest humoral and cellular immunity. A booster with mRNA vaccine resulted in increases in median levels of IgG-Spike antibodies and IFN-γ as compared to those of two-dose of any vaccine. Humoral and cellular immunity levels were significantly higher in participants with previous infection compared to those without infection. Conclusions Heterologous vaccination (AZ/PZ) elicited the strongest immunity among the two-dose vaccination regimens. The immunity offered by the third-booster dose of SARS-CoV-2 vaccine depends not only on the type of vaccine administered but also on previous doses and prior infection. Previous exposure to SARS-CoV-2 antigens by infection strongly affect immunity of vaccinated individuals.